2016
DOI: 10.4172/2165-7092.1000166
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Receptors for Advanced Glycation End Product in Pancreatic Carcinogenesis

Abstract: Pancreatic cancer is the fourth-leading cause of cancer deaths worldwide that considered as the malignant tumor with the poorest prognosis and the lowest survival rate. This extremely violent disease is rarely diagnosed at an early level and difficult to treat due to its resistance to radiation therapy and chemotherapy. Here, we show that the receptor for advanced glycation end products (RAGE) and its ligands, advanced glycation end products (AGEs), high-mobility group box 1 (HMGB1) and S100 protein family are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…AGEs are collective name given to proteins, lipids and nucleic acids that undergo irreversible modification by reducing sugars or sugar-derived products [25]. It has been reported that the AGEs and AGE receptors interaction would stimulate the growth of human pancreatic cancer via the autocrine induction-derived growth factor-B [26]. Another study also reported that AGEs triggered the growth and migration of culture human melanoma cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…AGEs are collective name given to proteins, lipids and nucleic acids that undergo irreversible modification by reducing sugars or sugar-derived products [25]. It has been reported that the AGEs and AGE receptors interaction would stimulate the growth of human pancreatic cancer via the autocrine induction-derived growth factor-B [26]. Another study also reported that AGEs triggered the growth and migration of culture human melanoma cells [27].…”
Section: Discussionmentioning
confidence: 99%